Analisis Risiko Kandungan Logam Kromium Heksavalen (Cr6+) Dan Arsen (As) Dalam Air Minum - Ahmad Mursidi (Jurnal Vokasi Kesehatan, 2015)
Abstract: Risk Analysis Metal Content of Hexavalent Chromium (Cr6 +) and arsenic (As) in drinking water. The research objective is to determine estimates of health risks from exposure to hexavalent chromium metal and arsenic in drinking water. Research conducted on Kalanganyar population that uses clean water supply wells for drinking water as many as 200 people, and the examination of samples of drinking water as many as 32 samples. Design research using cross-sectional design using the descriptive-analytic method. The results showed that the percentage of respondents who have a non-cancerous disease risk due to exposure to hexavalent chromium (RQ≥1) by 16%, while the percentage of respondents that have exceeded the risk of non-cancer diseases due to exposure to arsenic (RQ≥1) by 59%. The risk of cancer due to arsenic exposure on average the respondents amounted to 1.5 per 10,000 population. The concentration of hexavalent chromium has relation with health risk (p <0.05) with r = 0.927. Arsenic concentrations also have a relationship with a health risk (p <0.05) with r = 0.936.Abstrak : Analisis Risiko Kandungan Logam Kromium Heksavalen (Cr6+) Dan Arsen (As) Dalam Air Minum. Tujuan penelitian yaitu untuk mengetahui perkiraan risiko kesehatan akibat pajanan logam kromium heksavalen dan arsen dalam air minum. Penelitian dilakukan terhadap penduduk Kalanganyar yang menggunakan sarana air bersih sumur gali sebagai sumber air minum sebanyak 200 orang, dan pemeriksaan sampel air minum sebanyak 32 sampel. Rancang penelitian menggunakan desain Cross Sectional dengan menggunakan metode deskriptif analitik. Hasil penelitian menunjukkan bahwa persentase responden yang mempunyai risiko penyakit non kanker akibat pajanan kromium heksavalen (RQ≥1) sebesar 16%, sedangkan persentase responden yang telah melampaui batas risiko penyakit non kanker akibat pajanan arsen (RQ≥1) sebesar 59%. Besar risiko kanker akibat pajanan arsen rata-rata pada responden sebesar 1,5 per 10.000 penduduk. Konsentrasi kromium heksavalen terbukti mempunyai hubungan dengan risiko kesehatan (p < 0,05) dengan nilai r = 0,927. Konsentrasi arsen juga mempunyai hubungan dengan risiko kesehatan (p < 0,05) dengan nilai r = 0,936.